Determinación de hemoglobina y hematocrito en personas adultas entre 18 a 60 años de edad que pertenecen a la Iglesia Adventista “Nueva Jerusalén” del distrito de Florencia de Mora, agosto 2011 - Delgado Espinoza, Ricardo Michel (2012)
This work was aimed the determinationofhemoglobin and hematocritin 75adultsof both sexbelonging tothe Adventist church"New Jerusalem"of the District ofFlorencia de Mora, carrying out ahealthtalkon the subject, distributing information leafletsandencouraging them toperformreview ofhemoglobin andhematocrit, the blood samplewasobtainedfasting, applying a survey tocollect information aboutpersonal data, vital signs, nutritional aspect, socioeconomic, lifestyle and health. The determination of Hemoglobin wasby the colorimetric method, leading to readthe sampleto the spectrophotometerat 540nm,andthe method for hematocrit to microescale. Los results were analyzed usingthe nonparametric testof independence ofcriteria usingthedistribution chi-squareand Pearsoncorrelation. The 83%of all womenand 86% of men arewith normalhemoglobin andhematocrit. The 9%of patients withdecreased valuesin menand 15%in women.The 2%of all womenand 5%of all men, with increased values. There is no relationship between levels of hemoglobinand hematocritby sex andage, we obtained a correlation ofr= 0.89indicatinga dependency between the two variablesHband Hto